Avaliação das políticas de enfrentamento às mudanças climáticas do Ceará: trajetória e relações com o subsetor de geração de eletricidade por combustíveis fósseis - Lima, Sarah Lorrany da Cunha (2024)
Climate change represents one of the greatest threats to the continuity of life on planet Earth. In order for them to be stopped in time, it is urgent to adopt policies to combat, mitigate and adapt to climate change, which focus mainly on the anthropogenic activities that most contribute to the emission of greenhouse gasses. Emissions scenarios are different at international, national and regional levels, but one sector unites all three: Energy. In Ceará, electricity generation using fossil fuels is the economic subsector that contributes most to the state's emissions, even with the high potential for electrical generation using renewable sources. The present work aims to evaluate Ceará's climate policies and their relations with the most polluting subsector. To this end, the In-Depth Assessment, proposed by Rodrigues, was used as a theoretical-methodological approach, covering the axes of Context Analysis, Content Analysis and Institutional Trajectory. Data were collected using bibliographic and documentary research techniques. To understand the vision of key social actors regarding the existence of the public policies in question, 12 semi-structured interviews were carried out, distributed equally among employees of the State Superintendence for the Environment (SEMACE), scientists working in the area of climate change, activists of the socio-environmental movement and indigenous leaders of the Anacé ethnic group. The Discursive Textual Analysis methodology was used to analyze the textual content generated from the transcription of the interviews. As a result, it was possible to verify that the construction processes and, until then, implementation of Ceará's climate policies disregard citizen participation and, consequently, exclude the dimension of environmental justice. Furthermore, such policies do not have a significant contribution to combating climate change, since there are not sufficient legal instruments to execute and monitor them. To date, there is also no evidence of a targeted insertion in the fossil fuel electricity production subsector, as Ceará's economic development policies are not aligned with climate protection.